2011
DOI: 10.1016/j.jcma.2011.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Uterine arterial embolization in the management of severe post-partum hemorrhage: A successful rescue method to avoid peripartum hysterectomy

Abstract: UAE appeared to be a safe procedure. Hypomenorrhea was common after UAE treatment (55.6%), although regular menstruation returned successfully. Future pregnancy seemed possible, and without complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
13
1
Order By: Relevance
“…4 women had abdominal pain or lower back pain 2 women had urinary frequency, and 1 woman had the pelvic inflammatory disease. 10 In present study only 33.33% had hypomennorhoe and 58.33% had no complications.…”
Section: Discussioncontrasting
confidence: 38%
“…4 women had abdominal pain or lower back pain 2 women had urinary frequency, and 1 woman had the pelvic inflammatory disease. 10 In present study only 33.33% had hypomennorhoe and 58.33% had no complications.…”
Section: Discussioncontrasting
confidence: 38%
“…Postpartum hemorrhage (PPH) remains one of the leading issues in women's health today and is the leading cause of maternal death (Horng et al, 2011). There have been considerable advances reducing maternal mortality in the last several decades; however, the issue of PPH continues to be a problem in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Since the late 1960s, transcatheter arterial embolization procedures have been used to control pelvic hemorrhage secondary to trauma, malignancy, or radiation-induced bleeding (Horng et al, 2011). The first reported case of uterine artery embolization (UAE) used to control PPH was in 1979.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 UAE has become increasingly accepted as a minimally invasive uterine-sparing procedure, and studies including Horng's publication in this issue have reported the successful preservation of the uterus. 4,5 Furthermore, UAE may be one of the most frequently used and effective methods in the management of women with major obstetric hemorrhage with uterus preservation, 6 although sometimes, peripartum hysterectomy cannot be completely avoided for the purpose of saving a life. 7 The rate of peripartum hysterectomy use has significantly decreased recently, partly because of improvements in anesthesia, medicine, surgery, and even radiology.…”
mentioning
confidence: 99%